KREATIVITAS DAN KOLABORASI PESERTA DIDIK MELALUI PEMBELAJARAN BERBASIS PROYEK DI SMP UNGGULAN ZAINUL HASAN - Hidayatullah, Nuril; rahayu, Eka (ASMARALOKA: Jurnal Bidang Pendidikan, Linguistik, dan Sastra Indonesia, 2023)
The aim of this research is to describe the creativity and collaboration of students through project based learning at the superior Zainul Hasan Genggong Middle School. This research method uses qualitative research that uses descriptive data. The subjects of this research are the students of the superior Zainul Hasan Genggong Middle School. Data and data sources in This research is in the form of a project and students are creative in a collaborative way using secondary data. Based on the data collected, project learning by collaborating really helps students create projects creatively. The target of implementing this research is Zainul Hasan's superior secondary school students. Analysis of data collection techniques by reducing data and presenting data that has been obtained by researchers. The results of this research show that students are more creative in creating a project by collaborating which is carried out at the superior Zainul Hasan Genggong Middle School.